2009
DOI: 10.1093/toxsci/kfp146
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Toxicity of Multiwall Carbon Nanotubes in Rats Exposed for 3 Months

Abstract: Carbon nanotubes (CNT) are of great commercial interest. Theoretically, during processing and handling of CNT and in abrasion processes on composites containing CNT, inhalable CNT particles might be set free. For hazard assessment, we performed a 90-day inhalation toxicity study with a multiwall CNT (MWCNT) material (Nanocyl NC 7000) according to Organisation for Economic Co-operation and Development test guideline 413. Wistar rats were head-nose exposed for 6 h/day, 5 days/week, 13 weeks, total 65 exposures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
336
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(378 citation statements)
references
References 21 publications
26
336
2
11
Order By: Relevance
“…They found that MWNT induced massive loss of cell viability through DNA damage and programmed cell-death. Inhalation exposure of MWCNTs to rats were found to cause increased lung weights, pronounced multifocal granulomatous inflammation, diffuse histiocytic and neutrophilic inflammation, and intra-alveolar lipoproteinosis [18]. The genotoxicity of MWCNTs have also been investigated in our previous work [19].…”
mentioning
confidence: 99%
“…They found that MWNT induced massive loss of cell viability through DNA damage and programmed cell-death. Inhalation exposure of MWCNTs to rats were found to cause increased lung weights, pronounced multifocal granulomatous inflammation, diffuse histiocytic and neutrophilic inflammation, and intra-alveolar lipoproteinosis [18]. The genotoxicity of MWCNTs have also been investigated in our previous work [19].…”
mentioning
confidence: 99%
“…[17][18][19][20][21] On the other hand, the inhaled carbon nanomaterials may lead to stress, inflammation, lung insult and a variety of cardiovascular effects. [22][23][24][25][26][27][28] There are growing numbers of computational studies to investigate the mechanisms behind the spectrum of biological effects. Because of their well-defined structure, carbon nanomaterials also serve as the representative hydrophobic nanomaterials in the pioneering studies about the protein-nanomaterial interaction.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…The accuracy of d m as a measure of an aerosol's true size has been questioned, especially for irregularly shaped aerosols, such as those composed of carbon nanotubes (Ku et al 2007;Ma-Hock et al 2009). While the aerosols in this work are not spherical, as is assumed when d m is calculated, the particle morphology is noticeably more densely packed than are carbon nanotube aerosols.…”
Section: Particle Size and Size Distributionmentioning
confidence: 99%
“…When dispersed into a ∼500 L chamber, the ENPs produced number concentrations of 6.82 × 10 4 -1.40 × 10 6 , TABLE 2 Statistics of nanoparticle aerosols generated by various dry powder dispersion techniques. All values are number-weighted unless otherwise specified Primary for C 60 , 0.4 g cm −3 for TiO 2 , and 0.2 g cm −3 for CeO 2 ), these number concentrations translate into mass concentrations (Figure 4) that are of similar order of magnitude to those used for inhalation nanotoxicology studies (Ma-Hock et al 2009;Chen et al 2012;Kim et al 2012;Noel et al 2012). The actual densities of aerosol particles, however, are likely to be higher than the bulk powder densities since the primary particles appear tightly packed within the aerosols, as discussed below.…”
Section: Aerosol Number and Mass Concentrationmentioning
confidence: 99%
See 1 more Smart Citation